VERTICAL VIBRATIONS OF BASE ISOLATED MACHINEFOUNDATIONS (Journal of Engineering, 2010)
Vibration of base isolated machine foundations has been studied using the ScaledBoundary Finite Element Method (SBFEM) and the cone model method. Thedynamic stiffness of soil supporting rigid massless foundation was determined. Thisstiffness is of complex value. The real part represents the reflected energy of therestoring and inertial forces while the imaginary part represents the energy dissipatedwithin the endless extent of the soil as a geometric damping. The effect of geometricand material properties of soil upon the real and imaginary parts of the dynamicstiffness was determined and represented in terms of dimensionless charts for thefrequency range of interest. Results have shown that increasing the embedment ratiohas a significant effect on the dynamic stiffness, it increases the dynamic stiffnessconsiderably. The effect of stiffness ratio(stiffness of isolator/ stiffness of soil) wasdemonstrated for isolated machine foundations. The use of soft isolators reduces thedynamic response of foundation and the soil reaction